Effect of reinforcement to the square hollow section on the strength of foamed concrete beam - Dominic, Tiong Sie Huo (2019)
Foamed concrete with a density of 1600kg/m³ is now widely used as a structural component like slab due to it lighter than the normal concrete. Meantime, it helps in saving cost and reduce the use of formwork. The hollow section that implemented to beam is also an effort to make the structural lighter. Processed Spent Bleaching Earth (PSBE) is an industrial waste which possesses pozzolanic properties like a cement. PSBE used for partially replacing the content of the cement to make it more environmentally friendly. PSBE partially replaced cement up to 30% of the total weight of the cement content. The objective of this study is to analyse the effect of the reinforcement of hollow section on the strength, deflection and mode of failure of the foamed concrete beam. Three specimens prepared to investigate in this study. Specimen 1 can be known as a control beam which acts like a normal beam without a hollow section. Specimen 2 is the beam with a hollow section. Meanwhile, specimen 3 is the beam that added a steel bar around the hollow section to reinforcement the hollow section. The size of the beam was fixed to all specimen with (150 x 200 x 1500) mm. The hollow section that implements to both specimens were in the size of 50x50 mm to the center of the beam. Each specimen was prepared up to 3 unit of samples for testing to get the flexural strength, deflection and mode of failure. Three units of Linear Variable Displacement Transducer (LVDT) were used to measure the deflection of the beam. According to the result, specimen 1 (control beam) had the high strength to resist maximum loading of 31.003kN and flexural strength up to 6.201 N/mm². However, specimen 3 with reinforcement around the deflection can resist more deflection compared to the other specimens. The mode of failure for all the specimens considered as a shear crack as slide cracking pattern found. In short, the hollow section implemented to the beam had affected the strength and deflection of the beam even with added reinforcement around the hollow section. Therefore, it is essential in beam exhibited greater strength and reduce the deflection and cracking.